Is the silver generation still on the labour market or already inactive? The situation of the elderly on the Polish labour market - Knapińska, Magdalena (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The aim of the article is to determine the economic situation of people aged over 50 and the conditions of their professional activity. The subject of the analysis is the labour market of Poland – an EU Member State and of the OECD, a country that has undergone a political transformation from a centrally planned economy to a market economy. The research methods applied in the study included: literature analysis, methods of statistical analysis based on descriptive statistics tools, analysis of variability and logical analysis of cause and effect relationships. To achieve the aim of the article, several research questions were formulated. First of all, these addressed several issues: Is the population aged 50+ in Poland is still professionally active? What are the reasons for the decision to be professionally active or inactive? What factors influence changes in the number of pensioners? Is the situation of people aged 50+ on the Polish labour market different from their situation in other EU countries? The research methods used in this study are: literature analysis, statistical analysis method based on descriptive statistic tools, analysis of variability, and logical analysis of cause and effect relationship. By the way of conclusion, an attempt was also made to compare the situation in Poland with the models of life of the elderly in other European economies of such countries as Czechia, Germany, Sweden and Italy. The main findings were the following: the economic situation of the elderly in Poland deteriorated, their willingness to look for work and activity increased, but unfortunately this search was hindered by significant barriers to accessing the labour market. Recommendations for economic policy include demands to take specific actions to extend professional activity, facilitate access to digital job search methods, and social campaigns to counteract ageism.